Coping style and quality of life in patients with epilepsy: a cross-sectional study - Westerhuis, Willemien (Springer-Verlag, 2010)
Having epilepsy has a large impact on one's well-being, but often seizure frequency and severity do not explain self-reported quality of life. We hypothesized that one's personal coping style is more important. In this study, 105 patients attending the outpatient neurological clinic at the University Medical Centre in Utrecht, the Netherlands, with a diagnosis of partial epilepsy, aged 17–80 years, completed questionnaires. Demographic information, disease characteristics, health-related quality of life (HRQoL), and coping styles were obtained by postal-validated HRQoL questionnaires: the EQ5D and RAND-36 and the Utrecht Coping List. A passive coping style explained 45% of the variance in the mental component of HRQoL and was more important than ‘objective’ seizure-related measures. Confounders such as employment, gender, and side-effects of treatment explained another 6%. Passive coping style also influenced the physical component of the HRQoL, but here seizure-related factors predominated. Overall, epilepsy patients showed a more avoiding coping style, and female patients a less active coping style and more reassuring thoughts, compared to the Dutch population. The personal coping style of patients appears to be more important than seizure-related measures in predicting mental aspects of quality of life. Coping style characteristics rather than disease characteristics should guide clinical decision-making in patients with epilepsy. Further studies should investigate the effect on HRQoL of behavioral interventions to improve coping.